1996
DOI: 10.1002/(sici)1096-9861(19960930)373:4<484::aid-cne2>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional evidence for lesion-specific sprouting of corticostriatal input in the adult rat

Abstract: Previous studies in our laboratory have shown that cortical lesions induced by thermocoagulation of pial blood vessels, but not by acute aspiration, result in 1) the preservation of control levels of the growth-associated protein (GAP)-43 and 2) a prolonged increase in neurotransmitter gene expression in the denervated dorsolateral striatum. We have examined whether corticostriatal projections from the spared homotypic contralateral cortex contribute to these effects. Adult rats received either a thermocoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…In addition, Stroemer et al (1995) detected significantly elevated levels of synaptophysin in contralesional sensorimotor cortex at 14, 30, and 60 days after unilateral cortical infarction. Studies with an anterograde neuroanatomical tracer have shown axonal sprouting from the contralesional cortex to the ipsilesional striatum and to the perilesional cortex (Carmichael, 2003;Napieralski et al, 1996). As manganese is transported in both anterograde and retrograde directions (Pautler et al, 2003) and can be transferred transsynaptically (Pautler et al, 1998;Saleem et al, 2002), MEMRI allows visualization of wide-ranging neuronal networks, and not sole afferent or efferent projections.…”
Section: Enhanced Interhemispheric Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Stroemer et al (1995) detected significantly elevated levels of synaptophysin in contralesional sensorimotor cortex at 14, 30, and 60 days after unilateral cortical infarction. Studies with an anterograde neuroanatomical tracer have shown axonal sprouting from the contralesional cortex to the ipsilesional striatum and to the perilesional cortex (Carmichael, 2003;Napieralski et al, 1996). As manganese is transported in both anterograde and retrograde directions (Pautler et al, 2003) and can be transferred transsynaptically (Pautler et al, 1998;Saleem et al, 2002), MEMRI allows visualization of wide-ranging neuronal networks, and not sole afferent or efferent projections.…”
Section: Enhanced Interhemispheric Connectivitymentioning
confidence: 99%
“…This explains why we have found increased manganese enhancement in multiple contralateral regions. The enhanced transhemispheric manganese transfer may be explained by retrograde transport by newly formed or unmasked corticocortical (Allegrini and Wiessner, 2003;Carmichael, 2003), corticostriatal (Napieralski et al, 1996), and corticothalamic projections (Yu et al, 1995). Evidence for increased manganese transport in crossing white matter fibers was found in the corpus callosum.…”
Section: Enhanced Interhemispheric Connectivitymentioning
confidence: 99%
“…Cortex contralateral to the lesion, the origin of corticostriatal afferents which make up a population of reactive fibers in this model (Napieralski et al, 1996,Cheng et al, 1998,McNeill et al, 1999, and denervated ipsilateral striatum, a region of synaptic remodeling, were examined with regard to growth-associated protein expression. GAP-43 and SCG10 in these regions were not influenced by unilateral pump implantation with vehicle or SCH23390 infusion alone, but lesioning and SCH23390 infusion did alter growth-associated protein expression (Fig.…”
Section: Protein Expressionmentioning
confidence: 99%
“…For example, in studies in visual cortex of adult cats after retinal lesions and in somatosensory cortex of adult monkeys after peripheral nerve injury, anatomical rewiring was limited to a few millimeters (Darian-Smith and Gilbert, 1994;Florence et al, 1998). However, it appears that a cortical injury creates a particularly favorable environment for sprouting to occur in the remaining, intact cortex (Napieralski et al, 1996;Carmichael et al, 2005). Although anatomical reorganization also occurs in the cortex immediately adjacent to a stroke-induced injury (Carmichael et al, 2001), the extension of this phenomenon to distant but interconnected areas has not been demonstrated in adult mammals.…”
Section: Introductionmentioning
confidence: 99%